Recent development of egg protein fractions and individual proteins as encapsulant materials for delivery of bioactives. (1st March 2023) - Zhang, Yue; Guo, Yunsi; Liu, Feng; Luo, Yangchao
Graphical abstract: Highlights: Egg proteins have shown great performance as encapsulant materials. The main egg protein-based delivery systems and their fabrication mechanisms are described in detail. Novel applications on protection/delivery of bioactives, probiotics, and metal NPs are summarized. Current challenges and future trends of egg protein encapsulants are discussed. Abstract: Egg proteins, as one of the most abundant animal protein sources, have received considerable attention for developing delivery systems. Among all egg proteins, egg white (ovalbumin) is the most promising encapsulant due to its excellent properties such as gelling, digestibility, self-assembly, amphiphilic nature. In this review paper, we focused particularly on egg protein-based delivery systems with superior encapsulation and delivery functions, including polymeric nanoparticles, emulsions, hydrogels and aerogels. Egg protein-based delivery systems across a wide range of geometry and dimensions have been applied to protect or control-release bioactive small molecules and macromolecules, probiotics and metal nanostructures. However, there are challenges that must be carefully addressed for advancing the practical applications of egg protein-based delivery system in foods, including allergenicity from ovalbumin and ovotransferrin, intolerance to environmental conditions, limited processing technologies. More efforts are warranted to fill knowledge gaps related to fabrication, utilization and digestive mechanisms of egg protein-derived delivery systems.